Categorial Field of Research of the Problem of Moral Education of Pupils - Viktor Korolenko (Pedagogical Discourse, 2015)
On the basis of the analysis of psychological and pedagogical sources moral categories are described in the article. Importance of influence of moral education on the general education of children of school age is well-proven. Ability of the effective use of modern pedagogical knowledges is underlined. The results of the conducted research specify on the necessity of elucidation to the children of moral categories which are instrumental in aspiring of growing up personality to moral perfection.The conducted research proves that moral education is a process, directed on development of integral personality of child (love to Motherland, positive attitude toward society, collective, people, to labour, duties). The basis of moral education is in that socially necessary requirements of society, stimulating personal qualities of every child, such as debt, honour, conscience, dignity.Moral education is one of the main components of educational process at school. Purposeful pedagogical activity is instrumental in development of moral qualities of personality and it helps to find them the place in the society (using the received knowledge and abilities in life).